2007
DOI: 10.3189/172756507781833839
|View full text |Cite
|
Sign up to set email alerts
|

Investigating surface movements of debris-covered Miage glacier, Western Italian Alps, using dendroglaciological analysis

Abstract: Dendroglaciological analysis of supraglacial trees represents an example of applied dendro- geomorphological methods in reconstructing glacier variations. Supraglacial trees react to glacier ice and debris movement, assuming typical shapes with modified radial growth. In this paper, based on treering analysis of Larix decidua Mill., we investigate the relationship between the distribution and growth of trees located on the most famous and representative debris-covered glacier in the Italian Alps (Miage glacier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 23 publications
0
64
0
1
Order By: Relevance
“…The debris of DCGs therefore differs from the fine wind-blown particles that constitute the cryoconite, the most abundant debris in the central parts of debris-free glaciers (Laybourn-Parry et al, 2012). The debris is then transported down valley for times that, on some glaciers, can be as long as a century (Pelfini et al, 2007). As a result, the glacier surface is covered by a continuous debris layer, whose thickness generally increases toward the glacier terminus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debris of DCGs therefore differs from the fine wind-blown particles that constitute the cryoconite, the most abundant debris in the central parts of debris-free glaciers (Laybourn-Parry et al, 2012). The debris is then transported down valley for times that, on some glaciers, can be as long as a century (Pelfini et al, 2007). As a result, the glacier surface is covered by a continuous debris layer, whose thickness generally increases toward the glacier terminus.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the glacier surface is covered by a continuous debris layer, whose thickness generally increases toward the glacier terminus. The long transport on the glacier surface allows debris weathering and alteration, and its colonization not only by microorganisms but also by animals (for example, arthropods) and plants (Pelfini et al, 2007(Pelfini et al, , 2012Caccianiga et al, 2011;Gobbi et al, 2011). Ecological communities therefore exist on the surface of DCGs, and may be structured according to a chronosequence, with communities increasing in complexity towards the glacier terminus (Gobbi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that, while DCGs can be considered among the continental glacier environments richest in life, the ecological conditions in their debris may pose adverse and stressful conditions to soil organisms. In fact, these habitats are characterized by substrate instability due to the glacier motion (up to 76 m per year, on the Miage Glacier; Pelfini et al 2007) and rather short exposure of sediments to weathering (less than one century; Pelfini et al 2007) that prevent the evolution of a supraglacial soil and enrichment in organic matter. Moreover, the debris coverage is characterized by large daily and annual temperature variations (Mihalcea et al (2008) reported temperature excursions of up to +50°C on the Miage Glacier), which probably negatively affect soil meiofauna because only very eurythermic species can survive in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…The thick debris cover of DCGs reduces ice ablation (Nakawo & Rana 1999), but the debris surface can be heated by solar radiation to temperatures that can exceed +30°C (Brock et al 2010). During the long transport on the glacier surface, the debris is weathered and altered, and can be colonized by microorganisms (Franzetti et al 2013), plants (if the glacier elevation is lower than the treeline; Pelfini et al 2007Pelfini et al , 2012Caccianiga et al 2011) and animals (Gobbi et al 2011). It is important to note that not only pioneer organisms can live on the surface of DCGs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation